THE DIFFERENCES BETWEEN WINNING AND DEFEATED FOOTBALL TEAMS WHILE PERFORMING VARIOUS ACTIVITIES WITH A BALL - Miroslav Smajić; Slavko Molnar; Miroslav Radoman (Sport Scientific And Practical Aspects, 2025)
The aim of research is establishing qualitative differences between winning and defeated football teams while doing different activities with a ball. This research has shown and confirmed that successful football teams (the winner) are statistically better at activities with a ball which enabled them to play more successfully, i.e. the teams which are well-prepared in terms of technique and tactic and they used that in the game and finally won the game. The results of this research allow the insight into the model (character and qualitative structure) of technical and tactical efficiency of winning football teams (i.e. successful teams) taken from the games of particular groups of matches and then comparing this model with specific technical and tactical possibilities of the certain team (with necessary caution) aiming greater efficiency and qualitative restructuring technical and tactical elements in the training process of footballers in order to develop better model of the game and increase the effect of training.